THE RELATIONSHIP OF ELDERLY BEHAVIOR WITH VISIT COMPLIANCE AT THE ELDERLY POSYANDU REVIEW FROM THE HEALTH BELIEF THEORY IN THE POMALAA PUSKESMAS AREA: Elderly behavior - Ridhayani Djabar; Tasnim Tasnim; Sanihu Munir (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: An increase in the proportion of the elderly tends to be followed by an increase in health problems caused by degenerative processes. Data from the Kolaka District Health Officein 2019 the number of elderly was 14,440 and those who received health services were 3,547 (24.6%).The low level of health services for the elderly is caused by several factors. This research aims to analyzing the relationship between elderly behavior and compliance with visiting the Posyandu for the elderly in terms of health belief model theory in the Pomalaa Health Center area, Kolaka Regency. Methods: This type of research is a cross sectional study conducted from March to April 2021,the sample used are 256 respondents taken by simple random sampling. Result: Using Chi Square Test. The perceived value of vulnerability isX2count = 26,095 > X2table = 3.841, the value of perception of seriousness is X2count = 34,132 > X2table = 3.841, the value of perceived benefit is X2count = 47,026 > X2table = 3.841, the value of perceived obstacle isX2count = 83,542 > X2table = 3.841, the value of intention isX2count = 15.252 > X2table = 3.841. Conclusion: There is a relationship between perceptions of vulnerability, seriousness, benefits, barriers, and intentions with compliance with visiting the elderly at the elderly posyandu in the Pomalaa Health Center area, Kolaka Regency.